Evolution of Iceberg A68 since Its Inception from the Collapse of Antarctica’s Larsen C Ice Shelf Using Sentinel-1 SAR Data - Shivangini Singh; Shashi Kumar; Navneet Kumar (Sustainability, 2023)
This research focuses on the evolution of the largest iceberg A68 and analyzes the trajectory using Sentinel-1 SAR data. The monitoring began when A68 calved Larsen C Ice shelf on 12 July 2017, and ended on 1 February 2021. A total of 47 images were analyzed and studied to ascertain the changes in the area, trajectory and the factors that might have influenced said changes. The big size of the iceberg caught the scientific community’s attention when it started moving towards South Georgia Island, a habitat of penguins and seals. The pattern of decrease and increase in the iceberg’s size was analyzed and compared with the surrounding sea ice extent to account for longitudinal stretching and shrinkage. Iceberg’s trajectory was also studied to take into account the underlying seabed and ice rises, and their implication on A68’s maneuverability, giving rise to unique motions in the coastal regime. Two subsequent calving events in the iceberg were distinctly observed in March 2019 and April 2020. Since its inception up to December 2019, its drift was fairly gradual, with the pick up in pace observed upon its entry into open waters and departure from the peninsular region. The decrease in size was also fairly gradual with only two main calving events, as mentioned above. The cold water and sea ice surrounding the iceberg potentially helped maintain a steady state. Post its sojourn into the Southern Ocean, major calving began in December 2020 and continued through January 2021. This study explores the potential of SAR remote sensing in iceberg monitoring and tracking.